Parity Dominates Preeclampsia Risk Among Third Trimester Pregnancies: Paritas Mempengaruhi Risiko Preeklampsia pada Kehamilan Trimester Ketiga - Astutik ashari; Hesty Widowati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Preeclampsia remains a major contributor to maternal mortality and morbidity worldwide, particularly in developing countries, and continues to challenge antenatal health services. Specific Background: In Indonesia, the incidence of preeclampsia is substantial, and clinical observations indicate that maternal characteristics such as parity, body mass index (BMI), and antenatal care (ANC) attendance are frequently associated with its occurrence. Knowledge Gap: Previous findings have shown inconsistencies regarding the magnitude and pattern of associations between these maternal factors and preeclampsia, necessitating further contextual evidence from local healthcare settings. Aims: This study aimed to examine the relationship between parity, BMI, and ANC history with preeclampsia among third trimester pregnant women at a hospital in Sidoarjo. Results: Using a cross-sectional analytic design with 250 respondents selected through simple random sampling, chi-square analysis demonstrated statistically significant associations for parity (p=0.022), BMI (p=0.000), and ANC history (p=0.000). Primigravida mothers had 2.157 times higher odds of preeclampsia compared to multigravida, while obesity and incomplete ANC were also significantly associated. Novelty: This study provides updated hospital-based evidence quantifying comparative odds across three maternal factors within a single analytic model. Implications: Strengthening antenatal surveillance, nutritional monitoring, and targeted counseling for first pregnancies may support maternal health strategies aimed at reducing preeclampsia-related complications. Highlights: First pregnancy status showed the highest odds ratio among examined maternal characteristics. Obesity category demonstrated a statistically significant association in chi-square testing. Incomplete pregnancy checkups were linked with higher occurrence proportions in the observed cohort. Keywords:Parity; Body Mass Index; Antenatal Care; Preeclampsia; Maternal Health